Sequential information processing in persuasion - Linne, Roman; Hildebrandt, Jannis; Bohner, Gerd; Erb, Hans-Peter (Frontiers in Psychology, 2022)
We present a theory of sequential information processing (SIP) in social influence. It extends assumptions of the heuristic-systematic model, in particular the idea that information encountered early in a social influence situation may affect the processing of subsequent information. SIP also builds on the abstraction from content-related dichotomies in accord with the parametric unimodel of social judgment. SIP features four main assumptions: (1) Persuasion is the sequential processing of information that is relevant to judgment formation. (2) Inferences drawn from initial information may bias the processing of subsequent information if they are either activated logical rules (= syllogisms) or valence expectations that are relevant to the subsequent information. (3) Inferences drawn from initial information are resistant to change. Thus, the interpretation of subsequent information is assimilated to inferences drawn from the initial information. Or, if it is impossible to assimilate inferences, contrast effects occur. (4) For the overall effect of a persuasion attempt, the inferences from the involved information are integrated into an attitude judgment. We illustrate SIP by an experiment (N = 216) on assimilation and contrast effects based on processing sequence in which across sequence conditions exactly the same arguments were presented. Specifically, when an initial argument was followed by an argument of opposite valence (vs. a neutral argument), contrast (vs. assimilation) effects occurred on post-message attitudes. We discuss theoretical and applied implications of order effects for social influence phenomena, as well as challenges for further research developing and testing the theory.